Update Breast Cancer 2023 Part 3 – Expert Opinions of Early Stage Breast Cancer Therapies - Kolberg, Hans-Christian; Hartkopf, Andreas D.; Fehm, Tanja N.; Welslau, Manfred; Müller, Volkmar; Schütz, Florian; Fasching, Peter A.; Janni, Wolfgang; Witzel, Isabell; Thomssen, Christoph; Beierlein, Milena; Belleville, Erik; Untch, Michael; Thill, Marc; Tesch, Hans; Ditsch, Nina; Lux, Michael P.; Aktas, Bahriye; Banys-Paluchowski, Maggie; Kolberg-Liedtke, Cornelia; Wöckel, Achim; Harbeck, Nadia; Stickeler, Elmar; Bartsch, Rupert; Schneeweiss, Andreas; Ettl, Johannes; Krug, David; Taran, Florin-Andrei; Lüftner, Diana; Würstlein, Rachel (Geburtshilfe und Frauenheilkunde, 2023)
The St. Gallen (SG) International Breast Cancer Conference is held every two years, previously in St. Gallen and now in Vienna. This year (2023) marks the eighteenth edition of this conference, which focuses on the treatment of patients with early-stage breast carcinoma. A panel discussion will be held at the end of this four-day event, during which a panel of experts will give their opinions on current controversial issues relating to the treatment of early-stage breast cancer patients. To this end, questions are generally formulated in such a way that clinically realistic cases are presented – often including poignant hypothetical modifications. This review reports on the outcome of these discussions and summarises the data associated with individual questions raised.In einem 2-jährigen Rhythmus fand in St. Gallen in früheren Jahren und nun in Wien die „St. Gallen (SG) International Breast Cancer Conference“ statt. Dieses Jahr (2023) wurde diese Konferenz, die sich mit der Behandlung von Patientinnen in Frühstadien des Mammakarzinoms beschäftigt, zum 18. Mal durchgeführt. Am Ende dieser 4-tägigen Veranstaltung wird eine Panel-Abstimmung abgehalten, bei der ein Expertengremium über aktuelle kontroverse Themen bei der Behandlung von Brustkrebspatientinnen in Frühstadien abstimmt. Hierbei werden die Fragen meistens so formuliert, dass klinisch realistische Fälle – oft in verschiedenen Modifikationen – vorgestellt werden. Diese Übersichtsarbeit berichtet von den Abstimmungsergebnissen und fasst die mit den jeweiligen Fragen verbundene Datenlage zusammen.
Keywords: breast cancer; therapy recommendation; chemotherapy; endocrine therapy